Comparison of the chromosome banding pattern in the 2n = 56 cytotypes of Nannospalax leucodon and N. xanthodon from Turkey - Arslan, Atilla; Arısoy, Apdil; Zima, Jan (TheScientificWorldJournal, 2014)
We present the karyotype characteristics of five cytotypes of mole rats (Nannospalax) with 56 chromosomes revealed by the C-banding and AgNOR staining analyses. We attempt to investigate if the specific distinction between the populations from Thrace (N. leucodon) and Anatolia (N. xanthodon) is reflected also in their karyotypic differentiation. The specimens from each of the five populations studied revealed a distinct karyotype which was different from those found in other populations. The fundamental number of autosomal arms varied from 68 to 72. The amount of C-heterochromatin was larger in the Thrace sample of N. leucodon compared to the Anatolian population of N. xanthodon. The active NOR sites were recorded on five autosomal pairs in N. leucodon, whereas only three or four pairs bearing NOR were observed in N. xanthodon. Differences between the studied populations were quantified in the analysis of the distribution pattern of the C-positive bands and the AgNOR sites in individual chromosomes which indicated a basal position of the Thrace sample of N. leucodon and its divergence from other studied populations. The karyotypes of the 56-chromosome populations of N. leucodon and N. xanthodon are thus distinctly different.
Keywords: druhová specificita; Animals; Turecko; Chromosomes, Mammalian; zvířata; savčí chromozomy; Species Specificity; Chromosome Banding; Karyotype; Mole Rats; karyotyp; pruhování chromozomů; Turkey; mikroftalmičtí podzemní hlodavci